A scintillator for time-delay imaging, preparation method and application thereof
By using coated lanthanum-doped fluoride nanocrystals in time-delay imaging scintillation materials, the lack of performance of existing materials in high temperature and high humidity environments is solved, and the imaging effects of high resolution, long life and long delay time are achieved.
Patent Information
- Application Number
- CN202411746978.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2044-12-02
AI Technical Summary
Existing time-delay imaging scintillation materials exhibit low spatial resolution, short service life and short delay time in high temperature and high humidity environments, limiting their application in industrial defect detection and other fields.
The coated lanthanum element doped fluoride nanocrystals are used as scintillators, and the radiation resistance and thermal stability of the material are improved through inorganic glass, plexiglass or silica as the encapsulation layer.
It achieves the maintenance of excellent imaging performance in high temperature environments, improves spatial resolution, delay time and service life, and is suitable for time-delay imaging technology.
Smart Images

Figure CN119220260B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of scintillators and imaging technology, and in particular to a scintillator that can be used for time-delay imaging, a preparation method and an application thereof. Background Art
[0002] In industrial defect detection, it is crucial to ensure the safety and reliability of mechanical equipment, which requires evaluating the damage of materials or components at high temperatures. However, it is extremely difficult to build complex real-time X-ray imaging systems in harsh high-temperature environments. In addition, high temperatures can easily damage photodetectors, so it is necessary to develop strategies that can perform X-ray imaging in extreme temperature environments. In scintillator materials, delayed imaging technology uses the ability of materials to maintain their light emission properties for a certain period of time after being excited by radiation, generating continuous light signals. This feature enables delayed imaging to capture the same scene at multiple time points, thereby improving the signal-to-noise ratio of imaging and reducing background interference. In addition, delayed imaging can also capture rapidly changing events in dynamic scenes, and is suitable for fields such as biomedical imaging and security detection.
[0003] As the core components of X-ray time-delay imaging, scintillators of X-ray induced persistent fluorescence have sprung up like mushrooms after rain. For example, the literature (Wu S., Yuan L., et al., All-inorganic Mn2 + -doped metalhalide perovskite crystals for the late-time detection of X-rayafterglowimaging, Nanoscale 2023, 15, 13628-13634) reported manganese-doped metal halide perovskite crystals with X-ray time-delay imaging, which can be reactivated by 870 nm light or thermal stimulation after 72 hours of decay. The literature (Peng S., Chen L., et al., Precision X-Ray Time-Lapse Flexible Imaging from Fluoride Nanocrystals with the Constructed Deep Traps. Adv. Opt. Mater. 2023, 11, 2300752) reported Cs-doped metalhalide perovskite crystals for the late-time detection of X-rayafterglowimaging, Nanoscale 2023, 15, 13628-13634) reported manganese-doped metal halide perovskite crystals with X-ray time-delay imaging, which can be reactivated by 870 nm light or thermal stimulation after 72 hours of decay. 0.02 Na 0.98 LuF4:0.15Tb 3+However, most time-delay imaging scintillating materials focus on unencapsulated NCs or phosphors, both of which are severely limited by the high temperature and humidity of the surrounding environment, restricting their imaging spatial resolution, service life, and delay time.
[0004] In the field of industrial defect detection, the use of X-ray delayed imaging technology is essential to ensure the integrity of materials or components at high temperatures. The following is a detailed explanation of "both are severely limited by the high temperature and high humidity of the surrounding environment, which restricts their imaging spatial resolution, service life and delay time":
[0005] Effects of high temperature: High temperature environments can intensify chemical reactions on the surface of fluoride nanocrystals, especially when the material is exposed to oxygen or water vapor:
[0006] 1) Surface oxidation, rare earth doped fluoride nanocrystals, certain ions (such as Ce 3+ 、Eu 2+ ) is easily oxidized to Ce 4+ or Eu 3+ , causing the luminous properties to change or even disappear;
[0007] 2) The surface of fluoride nanocrystals may decompose or lose some fluoride ions, resulting in structural damage and increased surface defects;
[0008] 3) The defects on the surface of nanocrystals play a role in quenching luminescence. Unwrapped nanocrystals usually require ligands to repair surface defects. High temperature will damage the ligands on the surface of nanocrystals, reduce luminescence efficiency, and thus reduce scintillation performance.
[0009] Effect of high humidity: The effect of humidity in the air on unwrapped fluoride crystals is mainly reflected in:
[0010] 1) Surface hydrolysis: Fluoride nanocrystals usually have high surface energy and are prone to react with water molecules in the air, especially in an environment with high air humidity. The surface fluoride dissolves or partially dissociates to form hydrofluoric acid, which changes the surface structure and optical properties;
[0011] 2) Long-term exposure to humid air may cause phase change and agglomeration of fluoride nanocrystals.
[0012] Therefore, the development of new scintillator materials, especially those that can maintain excellent imaging performance under extreme conditions (high temperature), is the key to improving the application potential of delayed imaging technology. This patent aims to provide a scintillator delayed imaging system based on innovative materials to address the limitations of existing technologies and achieve more efficient and stable imaging performance. Summary of the invention
[0013] In the field of X-ray imaging technology, real-time X-ray imaging has a wide range of applications in health detection and non-destructive testing. In industrial defect detection, it is crucial to ensure the safety and reliability of mechanical equipment, which requires evaluating the damage of materials or components at high temperatures. However, it is extremely difficult to build complex real-time X-ray imaging systems in harsh high-temperature environments. In addition, high temperatures can easily damage photodetectors, so it is necessary to develop strategies that can perform X-ray imaging in extreme temperature environments. Time-delay imaging technology has emerged as a result. Compared with real-time imaging, time-delay imaging has incomparable advantages. It has a simplified imaging system, making it more suitable for harsh environments, especially high-temperature environments. However, most time-delay imaging scintillating materials are mainly concentrated on uncoated NCs or phosphors, both of which are severely limited by the high temperature and high humidity of the surrounding environment. Therefore, the development of new scintillator materials, especially those that can still maintain excellent imaging performance in extreme environments (high temperature and humidity), is the key to improving the application potential of time-delay imaging technology.
[0014] The present invention provides a scintillator that can be used for time-delay imaging. The scintillator is a coated lanthanum-doped fluoride nanocrystal, and the coating layer is any one of silicon dioxide, organic glass and inorganic glass.
[0015] The present invention also provides a method for preparing a scintillator that can be used for time-delay imaging, comprising the following steps:
[0016] The scintillator that can be used for time-delay imaging is prepared by using S1, S2 or S3:
[0017] The S1 method is used to prepare an inorganic glass-coated nanocrystalline scintillator, and the scintillator is prepared in the inorganic glass by a crystallization method, comprising the following steps:
[0018] Step S1-1: weigh glass raw materials in proportion, mix them thoroughly, transfer them to high temperature T1, and keep them warm for a period of time t1 until the mixed powder completely turns into a melt;
[0019] Step S1-2: obtaining a precursor glass by a melt quenching method, and annealing the precursor glass;
[0020] Step S1-3: The annealed glass in step S1-2 is transferred to a low-temperature furnace at a temperature of T2, and kept warm for a period of time t2, so that lanthanum-doped fluoride nanocrystals are precipitated inside the glass to obtain a scintillator.
[0021] The S2 method is used to prepare a nanocrystalline scintillator coated with organic glass, and the scintillator is obtained by mixing lanthanum-doped fluoride nanocrystals and organic glass, comprising the following steps:
[0022] Step S2-1: preparing lanthanum-doped fluoride nanocrystals by any one of a liquid phase method, a coprecipitation method, a solid solution method, and a solid phase method;
[0023] Step S2-2: weigh polymethyl methacrylate (PMMA), dissolve it in a solvent, and stir it thoroughly until the PMMA is completely dissolved to obtain a PMMA solution;
[0024] Step S2-3 introduces the nanocrystals in step S2-1 into the PMMA solution by solution mixing, and fully stirs the solution until the nanocrystals are evenly dispersed in the solution to obtain a uniform dispersion.
[0025] Step S2-4: Place the uniformly dispersed liquid in step S2-3 in a mold, and obtain a scintillator after solidification and molding.
[0026] The S3 method is used to prepare a silicon dioxide-coated nanocrystalline scintillator, wherein the silicon dioxide encapsulates the nanocrystal to obtain the scintillator, comprising the following steps:
[0027] Step S3-1: dissolving a silicon source in a solvent, adding a certain amount of aqueous ammonia, stirring and mixing, and forming a silicon dioxide precursor solution;
[0028] Step S3-2: taking the nanocrystals in step S2-1, and modifying the nanocrystals with any one of carboxylic acid and amine;
[0029] Step S3-3: adding the modified nanocrystals dropwise into the silica precursor sol, stirring and mixing evenly, and letting stand to obtain a sol;
[0030] Step S3-4: gelling and curing the above sol to obtain silica gel lanthanum doped fluoride nanocrystal scintillator.
[0031] In the above scheme, in the S1 method, the glass raw materials and molar ratio are: SiO2: 35-65%; K2CO3: 0-25%; Na2CO3: 0-25%; Al2O3: 10-35%; CaCO3: 0-8%; CsF3: 0-2%; LaF3: 0-8%; NaF: 0-30%; LuF3: 2-10%; TbF3: 0-8%; CeF3: 0-4%; ErF3: 0-1%; EuF3: 0-8%; BaF2: 0-30%; Al: 0-3%. The temperature T1 is 1350-1600 o C, temperature T2 is 400-700 o C, insulation time t1 is 1-2.5h, t2 is 1.5-6h.
[0032] In the above scheme, in the S2 method, the solvent is one or two of chloroform, dimethylformamide, and dimethyl sulfoxide.
[0033] In the above scheme, in the S3 method, any one of tetramethyl orthosilicate, sodium silicate, and 3-aminopropyltriethoxysilane is the silicon source.
[0034] In the above scheme, the inorganic glass coated nanocrystalline scintillator, the lanthanum element is any one of Tb, Eu, Er, Ce, Ce / Tb, and the fluoride nanocrystal is Na5Lu9F 32 , Cs 0.02 Na 0.98 Any of LuF4, Ba2LaF7.
[0035] In the above scheme, the organic glass or silicon dioxide coated nanocrystalline scintillator, the lanthanum element is any one of Tb, Gd / Tb, Ce, Ce / Tb / Gd, Ce / Tb, and the fluoride nanocrystal is Pb4Lu3F 17 ,Pb4Lu3F 17 , Pb4Lu3F 17 、Pb4Lu3F 17 Any of.
[0036] In the above scheme, the application temperature of the inorganic glass-coated nanocrystalline scintillator reaches 573K.
[0037] In the above scheme, the application temperature of the organic glass or silicon dioxide coated nanocrystalline scintillator reaches 423K.
[0038] Because the present invention adopts the above technical solution, it has the following beneficial effects:
[0039] 1. High resolution and clarity: The coated lanthanum-doped fluoride nanocrystal scintillator has excellent optical properties and can produce strong and stable luminescence under the action of X-rays or other high-energy radiation. This property helps to obtain high-resolution images in time-delay imaging, thereby improving the recognition of target details.
[0040] 2. Long afterglow life: Since the lanthanum-doped fluoride nanocrystal scintillating material in the coating layer usually has a long afterglow life, it can continue to emit light for a period of time after the initial excitation. This feature allows more time windows to be obtained during the imaging process to capture richer information.
[0041] 3. Radiation resistance and thermal stability: The coated lanthanum-doped fluoride nanocrystal scintillator usually has strong radiation resistance and thermal stability, and is suitable for long-term use in high temperature or radiation environments. In time-delay imaging, this stability helps to ensure consistent imaging effects during long-term observation.
[0042] 4. Fast response speed: The response speed of the coated lanthanum-doped fluoride nanocrystal scintillator is relatively fast, which is suitable for capturing dynamic changes and meeting the timeliness requirements of imaging. In addition, fast response can also reduce the signal loss caused by time delay, thereby improving signal strength.
[0043] 5. Flexible imaging process: Time-delay imaging technology can adjust the imaging delay time according to needs. The persistent luminescence characteristics of the coated lanthanum-doped fluoride nanocrystal scintillator provide support for this flexibility, which is particularly suitable for imaging applications that need to observe the time changes of specific processes.
[0044] 6. Both real-time and time-delay imaging: The scintillator of the present invention can achieve real-time imaging with high spatial resolution at room temperature, and can also achieve time-delay imaging, and has high application value and economic value.
[0045] In summary, these advantages make the coated lanthanum-doped fluoride nanocrystal scintillator have broad application potential and value in time-delay imaging in the fields of medicine, material testing, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] Figure 1 Schematic diagram of time-lapse imaging. Figure 1 (a) is a schematic diagram of storing target information at room temperature and then releasing the stored information under specific conditions (high temperature). Figure 1 (b) is a schematic diagram of storing target information under high temperature and then releasing the stored information under specific conditions (high temperature). Figure 1 Explanation of the numbers in the accompanying drawings: 1-X-ray tube, 2-scintillator, 3-camera.
[0047] Figure 2 The X-ray attenuation capability of the scintillator of Example 1 of the present invention is studied based on the XCOM database.
[0048] Figure 3 The X-ray attenuation capability comparison of the scintillators of Examples 1-4 of the present invention based on the XCOM database.
[0049] Figure 4 The scintillator obtained in Example 1 of the present invention has long afterglow spectra induced by X-rays at different temperatures.
[0050] Figure 5 This is a time-delay imaging picture of the scintillator applied to the chip and the standard plate in Example 1 of the present invention.
[0051] Figure 6 This is the time-lapse imaging of the scintillator in Example 1 of the present invention after being irradiated with X-rays for 5 minutes.
[0052] Figure 7This is the time-delay imaging of the standard plate under high temperature of the scintillator in Example 2 of the present invention.
[0053] Figure 8 For the implementation of 2 scintillator chip time-lapse X-ray imaging recorded over 24 to 168 hours. DETAILED DESCRIPTION
[0054] The following is a detailed description of the embodiments of the present invention. Although the present invention will be described and illustrated in conjunction with some specific embodiments, it should be noted that the present invention is not limited to these embodiments. On the contrary, modifications or equivalent substitutions made to the present invention should all be included in the scope of the claims of the present invention.
[0055] In addition, in order to better illustrate the present invention, numerous specific details are given in the following specific embodiments. It will be understood by those skilled in the art that the present invention can also be implemented without these specific details.
[0056] The present invention provides a scintillator that can be used for time-delay imaging. The scintillator is a coated nanocrystal.
[0057] The present invention provides a scintillator that can be used for time-delay imaging, wherein the nanocrystal is a fluoride nanocrystal doped with lanthanum.
[0058] In the above scheme, the wrapping layer is any one of silicon dioxide, organic glass and inorganic glass.
[0059] The present invention also provides a method for preparing a scintillator that can be used for time-delay imaging, comprising the following steps:
[0060] The scintillator that can be used for time-delay imaging is prepared by using S1, S2 or S3:
[0061] The S1 method is used to prepare an inorganic glass-coated nanocrystalline scintillator, and the scintillator is prepared in the inorganic glass by a crystallization method, comprising the following steps:
[0062] Step S1-1: weigh glass raw materials in proportion, mix them thoroughly, transfer them to high temperature T1, and keep them warm for a period of time t1 until the mixed powder completely turns into a melt;
[0063] Step S1-2: obtaining a precursor glass by a melt quenching method, and annealing the precursor glass;
[0064] Step S1-3: The annealed glass in step S1-2 is transferred to a low-temperature furnace at a temperature of T2, and kept warm for a period of time t2, so that lanthanum-doped fluoride nanocrystals are precipitated inside the glass to obtain a scintillator.
[0065] The S2 method is used to prepare a nanocrystalline scintillator coated with organic glass, and the scintillator is obtained by mixing lanthanum-doped fluoride nanocrystals and organic glass, comprising the following steps:
[0066] Step S2-1: preparing lanthanum-doped fluoride nanocrystals by any one of a liquid phase method, a coprecipitation method, a solid solution method, and a solid phase method;
[0067] Step S2-2: weigh polymethyl methacrylate (PMMA), dissolve it in a solvent, and stir it thoroughly until the PMMA is completely dissolved;
[0068] Step S2-3 introduces the nanocrystals in step S2-1 into the PMMA solution by mixing the solutions, and stirs the solution sufficiently until the nanocrystals are evenly dispersed in the solution.
[0069] Step S2-4: Place the uniformly dispersed liquid in step S2-3 in a mold, and obtain a scintillator after solidification and molding.
[0070] The S3 method is used to prepare a silicon dioxide-coated nanocrystalline scintillator, wherein the silicon dioxide encapsulates the nanocrystal to obtain the scintillator, comprising the following steps:
[0071] Step S3-1: dissolving a silicon source in a solvent, adding a certain amount of aqueous ammonia, stirring and mixing, and forming a silicon dioxide precursor solution;
[0072] Step S3-2: taking the nanocrystals in step S2-1, and modifying the nanocrystals with any one of carboxylic acid and amine;
[0073] Step S3-3: adding the modified nanocrystals dropwise into the silica precursor sol, stirring and mixing evenly, and letting stand to obtain a sol;
[0074] Step S3-4: gelling and curing the above sol to obtain silica gel lanthanum doped fluoride nanocrystal scintillator.
[0075] In the above scheme, in the S1 method, the glass raw materials and molar ratio are: SiO2: 35-65%; K2CO3: 0-25%; Na2CO3: 0-25%; Al2O3: 10-35%; CaCO3: 0-8%; BaCO3: 0-8%; CsF3: 0-2%; LaF3: 0-8%; NaF: 0-30%; LuF3: 2-10%; TbF3: 0-8%; CeF3: 0-4%; ErF3: 0-1%; EuF3: 0-8%; BaF2: 0-30%; Al: 0-3%. The temperature T1 is 1350-1600 o C, temperature T2 is 400-700 o C, insulation time t1 is 1-2.5h, t2 is 1.5-6h.
[0076] In the above scheme, in the S2 method, the solvent is one or two of chloroform, dimethylformamide, and dimethyl sulfoxide.
[0077] In the above scheme, in the S3 method, any one of tetramethyl orthosilicate, sodium silicate, and 3-aminopropyltriethoxysilane is the silicon source.
[0078] In the above scheme, the inorganic glass coated nanocrystalline scintillator, the lanthanum element is any one of Tb, Eu, Er, Ce, Ce / Tb, and the fluoride nanocrystal is Na5Lu9F 32 , Cs 0.02 Na 0.98 Any of LuF4, Ba2LaF7.
[0079] In the above scheme, the organic glass or silicon dioxide coated nanocrystalline scintillator, the lanthanum element is any one of Tb, Gd / Tb, Ce, Ce / Tb / Gd, Ce / Tb, and the fluoride nanocrystal is Pb4Lu3F 17 , Pb4Lu3F 17 , Pb4Lu3F 17 、Pb4Lu3F 17 Any of.
[0080] In the above scheme, the application temperature of the inorganic glass-coated nanocrystalline scintillator reaches 573K.
[0081] In the above scheme, the application temperature of the organic glass or silicon dioxide coated nanocrystalline scintillator reaches 423K.
[0082] Example 1
[0083] Step (1) accurately weighing the raw materials according to the molar ratio and fully mixing them, the composition of the glass is (a): 36SiO2-10K2CO3-26Al2O3-4CaCO3-18NaF-6LuF3-1TbF3 or (b) 55SiO2-16K2CO3-10Al2O3-2CaCO3-10NaF-6LuF3-4TbF3;
[0084] Step (2) The powder mixed in step (1) is subjected to a melt quenching method to prepare a precursor glass, and the melting temperature is set to 1550 o C, melting time is 1h.
[0085] Step (3) The precursor glass obtained in step (2) is transferred to an annealing furnace for annealing to eliminate internal stress. The annealing temperature is 450 o C, annealing time is 10h. The glass is then cut and polished to obtain the required size and shape.
[0086] Step (4) The polished glass in step (3) is transferred to a muffle furnace to perform a crystallization process on the glass. The crystallization temperature is 620 o C, the crystallization time is 2h. Finally, Na5Lu9F 32 :Tb 3+ of glass-ceramics, of which Tb 3+ The luminous center.
[0087] Example 2
[0088] Step (1) accurately weigh the raw materials according to the molar ratio and mix them thoroughly. The composition of the glass is (a): 45SiO2-20Na2CO3-15Al2O3-4CaCO3-6NaF-8LuF3-1CeF3-0.07ErF3-1.8Al or (b) 37SiO2-15Na2CO3-15Al2O3-7CaCO3-16NaF-8LuF3-1CeF3-0.1ErF3-1.8Al;
[0089] Step (2) The powder mixed in step (1) is subjected to a melt quenching method to prepare a precursor glass, and the melting temperature is set to 1400 o C, melting time is 1h.
[0090] Step (3) The precursor glass obtained in step (2) is transferred to an annealing furnace for annealing to eliminate internal stress. The annealing temperature is 300 o C, annealing time is 10h. The glass is then cut and polished to obtain the required size and shape.
[0091] Step (4) The polished glass in step (3) is transferred to a muffle furnace to perform crystallization on the glass. The crystallization temperature is 450 o C, the crystallization time is 6h. Finally, Na5Lu9F 32 :Ce 3+ / Er 3+ of glass-ceramics, of which Ce 3+ The luminous center.
[0092] Example 3
[0093] Step (1) accurately weigh the raw materials according to the molar ratio and mix them thoroughly. The glass composition is (a): 48SiO2-10Na2CO3-15Al2O3-20BaF2-5LaF3-1TbF3-1CeF3-1Al or (b) 38SiO2-18Na2CO3-20Al2O3-15BaF2-3LaF3-4TbF3-2CeF3-1.5Al;
[0094] Step (2) The powder mixed in step (1) is subjected to a melt quenching method to prepare a precursor glass, and the melting temperature is set to 1450 o C, melting time is 1h.
[0095] Step (3) The precursor glass obtained in step (2) is transferred to an annealing furnace for annealing to eliminate internal stress. The annealing temperature is 350 o C, annealing time is 10h. The glass is then cut and polished to obtain the required size and shape.
[0096] Step (4) The polished glass in step (3) is transferred to a muffle furnace to perform a crystallization treatment on the glass. The crystallization temperature is 480 o C, the crystallization time is 8h. Finally, Ba2LaF7:Ce 3+ / Tb 3+ of glass-ceramics, of which Ce 3+ / Tb 3+ The luminous center.
[0097] Example 4
[0098] Step (1) accurately weigh the raw materials according to the molar ratio and mix them thoroughly. The composition of the glass is (a): 45SiO2-10Na2CO3-15Al2O3-0.5CsF3-20.5NaF-8LuF3-1EuF3 or (b) 35SiO2-22Na2CO3-20Al2O3-1.5CsF3-10.5NaF-8LuF3-3EuF3;
[0099] Step (2) The powder mixed in step (1) is subjected to a melt quenching method to prepare a precursor glass, and the melting temperature is set to 1450 o C, melting time is 40 minutes.
[0100] Step (3) The precursor glass obtained in step (2) is transferred to an annealing furnace for annealing to eliminate internal stress. The annealing temperature is 350 o C, annealing time is 10h. The glass is then cut and polished to obtain the required size and shape.
[0101] Step (4) The polished glass in step (3) is transferred to a muffle furnace to perform crystallization on the glass. The crystallization temperature is 450 o C, the crystallization time is 8h. Finally, Cs 0.02 Na 0.98 LuF4:Eu 3+ of glass-ceramics, of which Ce 3+ The luminous center.
[0102] Figure 1This is a schematic diagram of time-delay imaging. After being irradiated by X-rays, all the information of the target object is stored in the scintillator. Figure 1 (a) is a schematic diagram of storing target information at room temperature and then releasing the stored information under specific conditions (high temperature). Figure 1 (b) is a schematic diagram of storing target information under high temperature and then releasing the stored information under specific conditions (high temperature).
[0103] Figure 2 This is a study of X-ray attenuation capability based on the XCOM database. GC20-4-600 in the figure is the sample of Example 1, BGO, YAG:Ce 3+ and YAPP:Ce 3+ As can be seen from the figure, the absorption of X-rays by the sample of Example 1 is comparable to that of BGO crystal, but better than that of YAG:Ce 3+ and YAPP:Ce 3+ This indicates that the crystal of the present invention is suitable for application in the field of digital medical imaging.
[0104] Figure 3 This is a comparative study of the X-ray attenuation capabilities of samples from Examples 1 to 4 based on the XCOM database. As can be seen from the figure, the scintillators obtained from different Examples have similar X-ray absorption capabilities despite slight edge differences. Figure 2 , indicating that the scintillator in the present invention has commercial potential.
[0105] Figure 4 The long afterglow spectra induced by X-rays at different temperatures after the sample of Example 1 was irradiated with X-rays. After the sample of Example 1 was irradiated with X-rays, the X-rays could further induce afterglow at high temperatures; in contrast, there was almost no afterglow at low temperatures. This shows that the scintillator of the present invention can be used for both real-time X-ray imaging at room temperature (no afterglow spectrum) and time-delay imaging (afterglow spectrum) stimulated by high temperatures.
[0106] After the scintillator and the target object obtained in Example 1 were pre-irradiated with X-rays for 5 minutes, the image of the target object could be displayed at high temperature. Figure 5 As shown, high-resolution imaging of the chip at 423 K maintained high visibility even after 6 seconds of decay. In addition, time-lapse imaging showed a high spatial resolution of up to 8 lp / mm. When the X-ray source was removed after 5 minutes of irradiation, imaging was still available even after 168 hours of decay when heated at 493 K, as shown in Figure 2. Figure 6 This highlights its great potential for application in high-temperature time-lapse imaging.
[0107] The scintillator sample obtained in Example 2 was irradiated with X-rays at 423 K for 5 minutes. After stopping the irradiation, a clear image of the chip was obtained by heating it to 523 K ( Figure 7 ), successfully demonstrated high-temperature X-ray time-lapse imaging. It is worth noting that the spatial resolution of time-lapse imaging is as high as 11lp / mm. In addition, the image information can be retained in the sample for a longer time, and accurate chip images can be obtained even after the sample has been exposed to ambient air at room temperature for up to 168 hours ( Figure 8 ).
[0108] These experimental results indicate that the scintillator of the present invention has great potential as a candidate for time-lapse X-ray imaging applications.
Claims
1. A method for preparing a scintillator that can be used for time-delay imaging, characterized in that: The following steps are involved: The method comprises the following steps: preparing a nanocrystalline scintillator coated with inorganic glass by using a crystallization method in inorganic glass; Step S1-1: weigh glass raw materials in proportion, mix them thoroughly, transfer them to a high temperature of 1350-1600°C, and keep them warm for 1-2.5 hours until the mixed powder is completely melted; Step S1-2: obtaining a precursor glass by a melt quenching method, and annealing the precursor glass; Step S1-3: transferring the annealed glass in step S1-2 to a low temperature furnace at a temperature of 400-700° C. and keeping the temperature for a period of 1.5-6 hours to precipitate lanthanum-doped fluoride nanocrystals inside the glass to obtain a scintillator; Glass raw materials and molar ratios are any of the following a or b: a: SiO2: 36%; K2CO3: 10%; Al2O3: 26%; CaCO3: 4%; NaF: 18%; LuF3: 6%; TbF3: 1%; b: SiO2: 55%; K2CO3: 16%; Al2O3: 10%; CaCO3: 2%; NaF: 10%; LuF3: 6%; TbF3: 4%.
2. The preparation method according to claim 1, characterized in that: The application temperature of the inorganic glass-coated nanocrystalline scintillator reaches 573K.
3. A method for preparing a scintillator that can be used for time-delay imaging, characterized in that: The following steps are involved: The method comprises the following steps: preparing a nanocrystalline scintillator coated with inorganic glass by using a crystallization method in inorganic glass; Step S1-1: weigh glass raw materials in proportion, mix them thoroughly, transfer them to a high temperature of 1350-1600°C, and keep them warm for 1-2.5 hours until the mixed powder is completely melted; Step S1-2: obtaining a precursor glass by a melt quenching method, and annealing the precursor glass; Step S1-3: transferring the annealed glass in step S1-2 to a low temperature furnace at a temperature of 400-700° C. and keeping the temperature for a period of 1.5-6 hours to precipitate lanthanum-doped fluoride nanocrystals inside the glass to obtain a scintillator; Glass raw materials and molar ratios are any of the following a or b: a: SiO2: 45%; Na2CO3: 20%; Al2O3: 15%; CaCO3: 4%; NaF: 6%; LuF3: 8%; CeF3: 1%; ErF3: 0.07%; Al: 1.8%; b: SiO2: 37%; Na2CO3: 15%; Al2O3: 15%; CaCO3: 7%; NaF: 16%; LuF3: 8%; CeF3: 1%; ErF3: 0.1%; Al: 1.8%.
4. The preparation method according to claim 3, characterized in that: The application temperature of the inorganic glass-coated nanocrystalline scintillator reaches 573K.
5. A method for preparing a scintillator that can be used for time-delay imaging, characterized in that: The following steps are involved: The method comprises the following steps: preparing a nanocrystalline scintillator coated with inorganic glass by using a crystallization method in inorganic glass; Step S1-1: weigh glass raw materials in proportion, mix them thoroughly, transfer them to a high temperature of 1350-1600°C, and keep them warm for 1-2.5 hours until the mixed powder is completely melted; Step S1-2: obtaining a precursor glass by a melt quenching method, and annealing the precursor glass; Step S1-3: transferring the annealed glass in step S1-2 to a low-temperature furnace at a temperature of 400-700° C. and keeping the temperature for 8 hours to precipitate lanthanum-doped fluoride nanocrystals inside the glass to obtain a scintillator; Glass raw materials and molar ratios are any of the following a or b: a: SiO2: 48%; Na2CO3: 10%; Al2O3: 15%; BaF2: 20%; LaF3: 5%; TbF3: 1%; CeF3: 1%; Al: 1%; b: SiO2: 38%; Na2CO3: 18%; Al2O3: 20%; BaF2: 15%; LaF3: 3%; TbF3: 4%; CeF3: 2%; Al: 1.5%.
6. The preparation method according to claim 5, characterized in that: The application temperature of the inorganic glass-coated nanocrystalline scintillator reaches 573K.
7. A method for preparing a scintillator that can be used for time-delay imaging, characterized in that: The following steps are involved: The method comprises the following steps: preparing a nanocrystalline scintillator coated with inorganic glass by using a crystallization method in inorganic glass; Step S1-1: weigh glass raw materials in proportion, mix them thoroughly, transfer them to a high temperature of 1350-1600°C, and keep them warm for 1-2.5 hours until the mixed powder is completely melted; Step S1-2: obtaining a precursor glass by a melt quenching method, and annealing the precursor glass; Step S1-3: transferring the annealed glass in step S1-2 to a low-temperature furnace at a temperature of 400-700° C. and keeping the temperature for 8 hours to precipitate lanthanum-doped fluoride nanocrystals inside the glass to obtain a scintillator; Glass raw materials and molar ratios are any of the following a or b: a: SiO2: 45%; Na2CO3: 10%; Al2O3: 15%; CsF3: 0.5%; NaF: 20.5%; LuF3: 8%; EuF3: 1%; b: SiO2: 35%; Na2CO3: 22%; Al2O3: 20%; CsF3: 1.5%; NaF: 10.5%; LuF3: 8%; EuF3: 3%.
8. The preparation method according to claim 7, characterized in that: The application temperature of the inorganic glass-coated nanocrystalline scintillator reaches 573K.
Citation Information
Patent Citations
High-transparency microcrystalline glass scintillator and preparation method and application thereof
CN111825332A
Fluoride nanocrystal, preparation method and application thereof
CN115368895A
Lutetium-based oxyfluoride scintillation glass as well as preparation method and application thereof
CN115572064A
Glass ceramic scintillator and preparation method and application thereof
CN118894650A